A simplified model for analyzing rainwater retention performance and irrigation management of green roofs with an inclusion of water storage layer. (15th January 2023) - Wang, Jun; Mei, Guoxiong; Garg, Ankit; Chen, Deqiang; Liu, Ning
Abstract: Rainwater retention and water content in green roofs are primarily influenced by structural configurations (i.e., soil layer, vegetation layer, and water storage layer) and climatic factors (i.e., rainfall and evapotranspiration (ET)). Based on the principle of water balance, this study proposes a conceptual model for simulating water flow in green roofs with water storage layers. Three green roof model experiments were conducted from August 1st, 2020 to July 31st, 2021 for calibrating and verifying the conceptual model. The proposed model was solved iteratively using a newly developed program in Visual Basic. The results showed that the conceptual model can capture the dynamic variations in the rainwater retention and water content of green roofs well. The average Nash-Sutcliffe efficiency coefficient is 0.65 and the average error is 6%. The annual rainwater retention capacity (RRC) of green roofs in the perennial rainy climate model was on average 28% higher than that in the seasonal rainy climate model. At the expense of water stress, high ET plants significantly increased the annual RRC of green roofs at a low level. As the water storage layer depth increased from zero to 150 mm, the annual RRC of green roofs increased by 41%, and the water stress decreased by 49%. Compared with an increase in water holding capacity and soil depth, the response of the annual RRC and water stress of green roofs for increasing water storage layer depth is much greater. As per climate of Southern China region, the water storage layer depth of 100 mm is found to obtain optimal rainwater retention and irrigation management in green roof with similar soil thickness (100 mm). Graphical abstract: Image 1 Highlights: A hydrological conceptual model of green roofs is proposed. Perennial rainfall increased rainwater retention by 28% versus seasonal rainfall. Rainwater retention is increased and irrigation is reduced with water storage layers. The optimal water storage layer depth is suggested as 100 mm.